Development-led globalization : towards sustainable and inclusive development paths - report to UNCTAD XIII (UN New YorkUS, 2011)
Sets out some of the main features of finance-driven globalisation and suggests that its outcomes have been much more uneven, unstable and unfair than its proponents had claimed or expected. Shows that there has been a systemic failure to create the enonomic environment needed to promote productive investment and employment. Outlines a rebalancing agenda which aims to deliver lasting and inclusive development gains. Sketches a three-pronged strategy focusing on a) building develomental states that are able to mobilise domestic resources, strengthen productive capacities and share the gains in an equitable manner; b) creating more robust mulilateral structures capable of forging collective responses to the challenges that countries will face in the years ahead, including those required to tame finance and to promote investment-led responses to climate change; and c) strengthening regional ties, including through South-South cooperation, in order to enhance stability and open new growth opportunities.
References: p.27-136.